Persistence and the German unemployment problem: empirical evidences on German labor market flows - Schmidt, Christoph M. (Discussion paper series, 1999)
Using a retrospective monthly calendarium of individuals' major economic activities, this paper characterizes the monthly employment and unemployment rates and the monthly transition intensities between the states of employment, unemployment, and out-of-thelabor- force for the German labor market between January/February 1983 and November/ December 1994. The analysis provides a detailed portrait for demographic cells defined by gender, three age groups, and three education groups. Overall, the German labor market displays a high level of persistence, but important differences exist across demographic groups. By contrast, almost no changes can be observed across time, apart from a drastic decrease of male job finding rates during the early 1990s. When compared to France, the German labor market does not appear to be excessively rigid, although the differences with the fluid US labor market are very substantial.
Keywords: Graue Literatur; Arbeitspapier; Statistik; Geschichte 1983-1994; Dauer; Arbeitslosigkeit; Deutschland